(untitled) (Research, Society and Development, 2021)
It is now well established in the literature that there is a need to incorporate the concept of sustainability into education at all study levels. However, there is considerable uncertainty expressed concerning how it could best be achieved and how the resilience concept would enhance this idea. This article aims to address this gap. The objective is to explore aspects of socio-ecological resilience, that underlies a university case study. The methodology is exploratory, descriptive, and explanatory. Results demonstrate that civil engagement university activities are an education approach that provides students with experiences that build skills necessary for addressing the challenges of the Anthropocene Epoch. The conclusion of the article emphasizes that the education for the Anthropocene epoch should consider the enhancement of ecosystem services by demonstrating that humans are part of the social-ecological systems; considering interdisciplinarity as a methodological approach; demonstrating the variety of potentials on participation of stakeholders by civil engagement as developing autonomy both on students and stakeholders and developing the ability for proactive attitudes. Is also enhance learning and social learning by civil engagement and participation.